Impact of radiation therapy facility volume on survival in patients with cancer. Issue 21 (16th August 2021) - Tchelebi, Leila T.; Shen, Biyi; Wang, Ming; Gusani, Niraj J.; Walter, Vonn; Abrams, Ross; Verma, Vivek; Zaorsky, Nicholas G.
Abstract : Background: This study examined whether radiation therapy facility volumes correlate with survival after curative intent treatment of solid tumors. Methods: The National Cancer Database was queried for patients with solid tumors treated with curative‐intent radiation therapy from 2004‐2013. Facilities were stratified into 4 volume categories: low, intermediate, high, and very high. Primary cancer sites were divided into neoadjuvant, adjuvant, or definitive radiation subgroups. Kaplan‐Meier curves of 5‐year postradiation survival probability, stratified by facility volume, were generated with log‐rank tests for group comparisons. Cox proportional hazard models were used to evaluate the effect of facility volume on survival, adjusted for multiple covariates. Results: There were 253, 422 patients treated at 1289 facilities: 6231 received neoadjuvant radiation, 147, 980 received adjuvant radiation, and 99, 211 received definitive radiation without surgery. Among patients receiving neoadjuvant radiation, survival correlated with facility volume for patients with rectal cancer (hazard ratio [HR], 0.75; 95% CI, 0.6‐0.94; P = .01). For cancers of the breast and uterus, patients receiving adjuvant radiation at very high‐volume facilities (vs low volume) had improved survival (HR, 0.83; 95% CI, 0.77‐0.90; P < .001 and HR, 0.77, 95% CI, 0.62‐0.97; P = .03, respectively). For patients receiving definitive radiation for prostate, non–small cell lung, pancreas, and head and neck cancer, there was an improvement in survival for patients treated at very high‐volume centers ( P < .05). Conclusions: For select cancer patients, treatment with curative radiation at higher volume facilities is associated with improved survival. In particular, patients receiving radiation therapy in the definitive setting without surgery may benefit most from treatment at high‐volume centers. Abstract : For select cancer patients, treatment with curative radiation at higher volume facilities is associated with improved survival. Metrics to ensure radiation therapy quality, such as centralized quality‐assurance checks or the integration of small‐volume facilities into larger health networks with mandated peer review, may be considered.